Pituitary Gland Involvement in Granulomatosis with Polyangitis - A Case Report - Azhar, Ayesha; Qadri, Ghulam Abbas; Khan, Saira; Basit, Bilal; Mir, Nighat; Sabir, Omer; Munir, Atif; Tarif, Nauman (Pakistan Journal of Kidney Diseases, 2021)
Granulomatosis with Polyangitis (GPA) is a multisystem disorder presenting usually with pulmonary and renal involvement. We present here a case GPA with pituitary gland involvement with diabetes Insipidus. She was diagnosed and responded to treatment with intranansla ddAVP. We here, discuss the case and review the literature in regards to the pituitary involvement in GPA.